A case of vasculitis case with unusual renal pathological findings presenting with rapidly progressing renal failure. Issue 12 (7th September 2020) - An, Hyo Jung; Jang, Ha Nee; Lee, Tae Won; Yoon, Changhyo; Park, Dong Jun; Bae, Eunjin
Abstract: Plasma cell infiltration may be an early lesion during renal invasion by ANCA‐associated vasculitis (AAV), and AAV should be considered in the differential diagnosis with acute renal failure and systemic symptoms. Abstract : Plasma cell infiltration may be an early lesion during renal invasion by ANCA‐associated vasculitis (AAV), and AAV should be considered in the differential diagnosis with acute renal failure and systemic symptoms.